A Golden Jubilee 1962-2012 souvenir album Tun Ahmad Sarji bin Abdul Hamid and Toh Puan Sagiyah binti Salikin (Archives of Tun Ahmad Sarji bin Abdul Hamid, 2012)
This souvenir album is produced to celebrate the golden jubilee of the marriage of the couple ; it charts their family and public life over the past 50 years, presenting a portrait of them, in their various capacities. Each page tells a story from their lives and brings together their favourite photos, documents and a few treasures.